The realibility of PISA in its evaluation of the mathematical competence - Moya Perez, J. A.; Ferrando, I. (Investigación en educación matemática XXI, 2020)
The realibility of PISA in its evaluation of the mathematical competence
Keywords: mathematical competence; PISA; WOS(2)